2019
DOI: 10.1002/nop2.295
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of perceived organizational support in the relationship between emotional labour and job attitudes: A study among health professionals

Abstract: Aim The present study was set out to establish the link between emotional labour (surface and deep acting) and job attitudes (job satisfaction organizational commitment) by introducing perceived organizational support as a moderating variable. Design The study made use of a cross‐sectional design by sampling three hundred and forty‐two (342) nurses and midwives from six health facilities in Ghana. Methods The study employed a quantitative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
3
25
1
2
Order By: Relevance
“…The present finding contradicts what scholars highlighted, that POS and job satisfaction have negative impacts on turnover intention (Eisenberger et al, 1990;Samad, 2006;Terason, 2018) and positive impact on organizational commitment (Eisenberger et al, 2002;Kang et al, 2018). Similar findings were reported by Lartey et al (2019) who observed the variables inversely, where POS failed to moderate the relationship between deep acting and job satisfaction. Our outcome adds to the inconsistent findings in the literature, we attributed this to our approach and context, more research is needed to uncover why such association exist.…”
Section: Discussionsupporting
confidence: 88%
“…The present finding contradicts what scholars highlighted, that POS and job satisfaction have negative impacts on turnover intention (Eisenberger et al, 1990;Samad, 2006;Terason, 2018) and positive impact on organizational commitment (Eisenberger et al, 2002;Kang et al, 2018). Similar findings were reported by Lartey et al (2019) who observed the variables inversely, where POS failed to moderate the relationship between deep acting and job satisfaction. Our outcome adds to the inconsistent findings in the literature, we attributed this to our approach and context, more research is needed to uncover why such association exist.…”
Section: Discussionsupporting
confidence: 88%
“…The present study is a follow-up to a previous study in Ghana that revealed that while surface acting was significantly related with job attitudes, deep acting did not [14]. Furthermore, the same study showed that perceived organisational support moderated the relationship between deep acting and job attitudes but did not play a moderating role in the relationship between surface acting and job attitudes [14].…”
Section: Introductionsupporting
confidence: 71%
“…The present study is a follow-up to a previous study in Ghana that revealed that while surface acting was significantly related with job attitudes, deep acting did not [14]. Furthermore, the same study showed that perceived organisational support moderated the relationship between deep acting and job attitudes but did not play a moderating role in the relationship between surface acting and job attitudes [14]. Even though empirical studies on emotional labour is emerging especially, in the African context, a study among media practitioners in Ghana asserted that emotional labour is conceptualised as faking (pretense and emotional enhancement) [12].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations